Preoperative Neoadjuvant Hormonal Therapy and Neoadjuvant Chemotherapy for Stage 3B and 4 Breast Cancer Patients in Dharmais Hospital-National Cancer Center, Indonesia: A Cohort Study - Karsono, Ramadhan; Purwanto, Denni Joko; Haryono, Samuel J.; Karsono, Bambang; Sari, Lenny; Pratiwi, Yulia; Aryandono, Teguh (Indonesian Journal of Cancer, 2018)
Background: There are no data of efficacy comparison between primary systemic therapy in stage 3B and 4 breast cancer patients in Indonesia. This study compared long term outcomes of breast cancer patients treated with neoadjuvant hormonal therapy (NAHT) and those treated with neoadjuvant chemotherapy (NACT)Methods: This was a cohort study conducted from 2011 to 2017. A total of 122 patients with stage 3B and 4 breast cancer received NAHT (n = 62) or NACT (n = 60) within a 6 cycles for NACT and 6 months for NAHT were included. Patients were excluded if they had a mastectomy before treatment, were pregnant, had been given hormonal therapy or chemotherapy before, had a contra-indication of chemotherapy, had a contra-indication of salpingo-oophorectomy bilateral for premenopausal patients, and declined to enter this study. The primary outcome of this study was overall survival. The outcomes were analysed using Kaplan-Meier for survival analysis and cox proportional hazard regression to estimate the hazard ratio.Results: There was a statistically significant difference in overall survival (p = 0.038). Median overall survival for NAHT patients was 1265 days and for NACT patients was 654 days. The hazard ratio showed NACT patients had a higher risk than NAHT patients (1.7 95% CI 1.03 – 2.9). Pathological complete response rate was higher in the NACT group than in the NAHT group (3.3% vs. 0%).Conclusions: Neoadjuvant hormonal therapy was superior to neoadjuvant chemotherapy in term of overall survival.